2001
DOI: 10.1159/000053808
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant <i>Dirofilaria immitis</i>-Derived Antigen Can Suppress Passive Cutaneous Anaphylaxis Reactions

Abstract: Background: High levels of antigen-nonspecific IgE are produced in animals infected with helminth parasites. Generally, the increase in IgE is thought to exacerbate allergic reactions. However, high levels of antigen-nonspecific IgE may alter some features of anaphylactic reactions. To investigate the molecular mechanisms of antigen-nonspecific IgE production induced during filarial infections, we previously constructed rDiAg (recombinant Dirofilaria immitis-derived antigen) in Escherichia coli. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
7
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…Our results were in agreement with the previous report of marked elevation of polyclonal IgE levels in the early phase of Nippostrongylus brasiliensis infections (5). The same phenomenon has also been observed in rats (10).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Our results were in agreement with the previous report of marked elevation of polyclonal IgE levels in the early phase of Nippostrongylus brasiliensis infections (5). The same phenomenon has also been observed in rats (10).…”
Section: Resultssupporting
confidence: 82%
“…Lee et al demonstrated that Ascaris suum pseudocoelomic body fluid contains a B cell mitogen (8) and induces high levels of total circulating IgE (9). We previously purified a factor from D. immitis that induces antigen-nonspecific IgE in mice and rats and named it DiAg (10). DiAg was identical to one already identified as a polyradderprotein, or neutrophil chemotactic factor (DiNCF; GenBank TM accession number D88757) (11).…”
mentioning
confidence: 99%
“…We previously purified a factor from Dirofilaria immitis that induces antigennonspecific immunoglobulin E (IgE) in mice and rats (2). We demonstrated that DiAg is an essential factor to induce antigen-nonspecific IgE in helminth infection.…”
mentioning
confidence: 99%
“…We demonstrated that DiAg is an essential factor to induce antigen-nonspecific IgE in helminth infection. Recombinant DiAg (rDiAg) is able to suppress passive cutaneous anaphylaxis (2). We concluded that antigennonspecific IgE protect against antigen-specific IgE by means of competition for mast cell receptors.…”
mentioning
confidence: 99%
“…DiAg monomer, the dominant ES product of the worm, can be divided into two types based on the difference of sequence on C-terminal half. We have previously found that DiAg monomer (either native [including V1 and V2] or recombinant [V1]) has the ability to induce nonspecific IgE synthesis (10,17,18,33,40). However, little is known about biological activities of another monomer (V2) and dimers.…”
Section: Discussionmentioning
confidence: 99%